(The effect of filler to the quality of aloe Powder) - Eko Susanto; wahyu Suryowidodo; Gasik Darma (Warta Industri Hasil Pertanian, 1992)
Aloe vera linn is neended in industries as rwa material for cosmetics, pharmacy and beverages.The types of aloe product which are available are in the form of gel,juice and powder.Aloe powder has more advantages in many cases than the other thypes.the research was conducted to study the-effect of filler in producing aloe powder.Fillers used were arabic gum and carboxyl methyl cellulose (CMC). The concentration of arabic gum applied was 1%,2% ,3% ,4%, and 5%,while the concentration of the mixed arabic gum and CMC was 2% with the ratio of 1:1,1:2,1:3,1:4,and 1:5.The best result was found with 2% filler of mixed  arabic gum and CMC with the ratio of 1:2,where pH was 5.25 and the ratio between product and the raw material was about 1:200.The viscosity of 2.50% of liqid from reconstitution of the aloe powder was 9.34 centipoise.